Human Premotor Corticospinal Projections Are Engaged in Motor Preparation at Discrete Time Intervals: A TMS-Induced Virtual Lesion Study - Fleischmann, Robert; Triller, Paul; Brandt, Stephan A.; Schmidt, Sein H. (Frontiers in Neuroergonomics, 2021)
Objectives: The significance of pre-motor (PMC) corticospinal projections in a frontoparietal motor network remains elusive. Temporal activation patterns can provide valuable information about a region's engagement in a hierarchical network. Navigated transcranial magnetic stimulation (nTMS)-induced virtual lesions provide an excellent method to study cortical physiology by disrupting ongoing activity at high temporal resolution and anatomical precision. We use nTMS-induced virtual lesions applied during an established behavioral task demanding pre-motor activation to clarify the temporal activation pattern of pre-motor corticospinal projections. Materials and Methods: Ten healthy volunteers participated in the experiment (4 female, mean age 24 ± 2 years, 1 left-handed). NTMS was used to map Brodmann areae 4 and 6 for primary motor (M1) and PMC corticospinal projections. We then determined the stimulator output intensity required to elicit a 1 mV motor evoked potential (1 mV-MT) through M1 nTMS. TMS pulse were randomly delivered at distinct time intervals (40, 60, 80, 100, 120, and 140 ms) at 1 mV-MT intensity to M1, PMC and the DLPFC (dorsolateral pre-frontal cortex; control condition) before participants had to perform major changes of their trajectory of movement during a tracing task. Each participant performed six trials (20 runs per trial). Task performance and contribution of regions under investigation was quantified through calculating the tracing error induced by the stimulation. Results: A pre-motor stimulation hotspot could be identified in all participants (16.3 ± 1.7 mm medial, 18.6 ± 1.4 mm anterior to the M1 hotspot). NTMS over studied regions significantly affected task performance at discrete time intervals (F(10, 80) = 3.25, p = 0.001). NTMS applied over PMC 120 and 140 ms before changes in movement trajectory impaired task performance significantly more than when applied over M1 (p = 0.021 and p = 0.003) or DLPFC (p = 0.017 and p < 0.001). Stimulation intensity did not account for error size (β = −0.0074, p = 1). Conclusions: We provide novel evidence that the role of pre-motor corticospinal projections extends beyond that of simple corticospinal motor output. Their activation is crucial for task performance early in the stage of motor preparation suggesting a significant role in shaping voluntary movement. Temporal patterns of human pre-motor activation are similar to that observed in intracortical electrophysiological studies in primates.